Patterned ground above the alpine timberline in the High Sudetes, Central Europe - Marek Křížek; David Krause; Tomáš Uxa; Zbyněk Engel; Václav Treml; Andrzej Traczyk (Journal of Maps, 2019)
Patterned ground in mountainous areas has a high palaeogeographic significance as it is associated with cold environments and frequently with permafrost conditions. Most patterned ground (i.e. sorted polygons, sorted nets, sorted stripes) in the High Sudetes is overgrown by vegetation and is relict. However, wind-blown summit areas with low snow cover allow for the activity of sorted circles, earth and peat hummocks, and some non-sorted stripes. The extent of patterned ground above the alpine timberline in the High Sudetes presented here is based on detailed field geomorphologic mapping. Patterned ground occurs on summit planation surfaces and surrounding gently sloping terrain, and covers 5.23 km2. Sorted polygons are the highest-elevated patterned-ground type. The spatial distribution of patterned ground is shown in the map, which could be helpful for future research of the Quaternary geomorphologic evolution of the mountain landscape and for nature protection planning in the High Sudetes.